Proceedings of the Conference in Honour of Murray Gell-Mann's 80th Birthday 2010
DOI: 10.1142/9789814335614_0047
|View full text |Cite
|
Sign up to set email alerts
|

CONFORMATION CHANGES AND PROTEIN FOLDING INDUCED BY ϕ4 INTERACTION

Abstract: A model to describe the mechanism of conformational dynamics in protein based on matter interactions using lagrangian approach and imposing certain symmetry breaking is proposed. Both conformation changes of proteins and the injected non-linear sources are represented by the bosonic lagrangian with an additional φ 4 interaction for the sources. In the model the spring tension of protein representing the internal hydrogen bonds is realized as the interactions between individual amino acids and nonlinear sources… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 6 publications
(9 reference statements)
2
9
0
Order By: Relevance
“…Having the total lagrangian in Eq. (1) at hand, one can derive immediately respective EOMs using Euler-Lagrange equation in term of ψ and φ [3],…”
Section: Dynamics Of Eomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having the total lagrangian in Eq. (1) at hand, one can derive immediately respective EOMs using Euler-Lagrange equation in term of ψ and φ [3],…”
Section: Dynamics Of Eomsmentioning
confidence: 99%
“…On the other hand, some previous studies have shown that the nonlinear excitations could play an important role in conformational dynamics of protein backbone by decreasing the effective binding rigidity of a biopolymer chain leading to a buckling instability of the chain [2]. The results motivate us to develop a model describing the conformational changes of protein based on the φ 4 theory [3]. The model is actually inspired by some previous models which attempt to reproduce the protein folding using nonlinear Schrödinger hamiltonian with the additional tension-like force [4,5].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to the previous case, the model adopts the φ 4 lagrangian but with additional interactions 15 ,…”
Section: Statistical Mechanics Observablesmentioning
confidence: 99%
“…(10) can be evaluated analytically using the Gaussian integral. This can be accomplished by rewriting it in term of Gaussian integral using the Fourier representation of Green's function to obtain the master equation 15 ,…”
Section: Statistical Mechanics Observablesmentioning
confidence: 99%